AutoCAD® 2007 and AutoCAD LT® 2007 : - Frey, David (Wiley Publishing, 2006)
AutoCAD 2007 and AutoCAD LT 2007: No Experience Required is the perfect step-by-step introduction to the world's leading CAD software. Inside this clear-cut guide are concise explanations and practical tutorials that explain how to plan and develop a complete AutoCAD project. Follow the tutorials sequentially, which have been fully updated for AutoCAD 2007, or jump in at any chapter by downloading the drawing files from the Sybex Web site. Either way, you'll quickly develop a solid grounding in the essentials and learn how to use AutoCAD's productivity tools to get your work done efficiently. The latest edition of this perennial topseller also covers AutoCAD's revamped 3D design features and includes a glossary and a supporting Web site with project files, bonus chapters, and appendices.